Stylistic diversity in the works of potter Hazem Al-Zoubi (Al-Academy, 2024)
The concept of stylistic diversity has an important role in reading contemporary literary and artistic texts, because it is an outlet for departing from the traditional framework of creative work, in which both the recipient and the producer interact in understanding and reproducing it. In turn, it helped to show many concepts related to artistic work from the outside because it is an important communicative and intellectual means. . The current research is to study the stylistic diversity among the sheep Hazem Al-Zoubi, which contained four chapters, the first chapter of which focused on the methodological framework of the research in stating the research problem, which was determined by answering the following question: - What is the stylistic diversity among the sheep Hazem Al-Zoubi? . Then comes the importance of research and the need for it to contribute to highlighting the stylistic diversity in the works of Al-Kharaf Hazem Al-Zoubi. It also contained the goal of the research, which is: identifying the stylistic diversity in the works of Hazem Al-Zoubi. The limits of the research were limited to studying the stylistic diversity in the works of the potter Hazem Al-Zoubi from (1985-2020), in addition to defining some of the terms mentioned in the research. The second chapter included the theoretical framework and previous studies. The theoretical framework contained two sections. The first section dealt with stylistic diversity conceptually. The second section is contemporary Jordanian ceramics. Then the indicators resulting from the theoretical framework. The third chapter included the research procedures, which included the research community, its sample, and the research tool, and the analysis of the research sample models. (5) models from the research community were intentionally chosen, while the indicators that resulted from the theoretical framework were adopted as criteria for analyzing those samples, and the descriptive approach was used for the analysis. As for the chapter The fourth contained results, conclusions, proposals, and sources. The researcher reached a set of results, including:1 - The potter relied on stylistic diversity to achieve interaction between the ceramic work and its surroundings.2- In his ceramic achievements, the potter borrowed vocabulary from the cultural heritage and also embodied the concept of nature through his multiple colors and various techniques in producing ceramic work